On system, several perspectives, many models - Henriksen, James O. (Proceedings of the 20th conference on Winter simulation, 1988)
This paper is a teaching piece. It is the latest in a series of papers by the author on the general subjects of modeling and problem solving. (See (Henriksen 1981), (Henriksen 1986), and (Henriksen 1987).) For the third year in a row, Dr. Alan Pritsker is also presenting a paper in a very similar vein. (See (Pritsker 1986), (Pritsker 1987) and (Pritsker 1988).) Section 1 presents a classic modeling problem first considered around the turn of the century (Lanchester 1916), long before the advent of digital computers. The system considered is a simplified battle between two opposing infantry forces. In subsequent sections, the battle is viewed from both a discrete-event and a continuous perspective. For each perspective, a variety of models is presented, and the comparative strengths and weaknesses of the various models are compared. For the student of modeling, the variety of models hammers home the point that for most modeling problems, one should consider several alternative perspectives before building a model.